2001
DOI: 10.1086/324352
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Human Immunodeficiency Virus Type 1 on Infectiousness of Tuberculosis: A Meta‐Analysis

Abstract: To assess if the relative infectiousness of patients with tuberculosis is enhanced by coinfection with human immunodeficiency virus type 1 (HIV-1), data from 6 studies of 1240 health care workers who had contact with tuberculosis patients were analyzed. Overall rates of tuberculin skin test conversion were similar regardless of HIV-1 positivity of tuberculosis patients (odds ratio [OR], 1.04; 95% confidence interval [CI], 0.23-1.84). However, when only 3 studies during nosocomial outbreaks of multidrug-resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
2
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 41 publications
2
50
2
2
Order By: Relevance
“…A meta-analysis of eight studies comparing the prevalences of TST positivity among household contacts of TB index cases found a lower rate of TST positivity among contacts of HIV-infected than among contacts of HIV-uninfected index TB cases (64). A cross-sectional study evaluating the prevalence of positive TSTs in pediatric contacts of adults with TB and HIV infection in Botswana found a lower proportion of TST positivity in children exposed to adult index cases with CD4 counts of Ͻ200 cells/l than in those exposed to index cases with CD4 counts of Ն200 cells/l (145).…”
Section: Does Hiv Alter the Transmission Dynamics Of Tb?mentioning
confidence: 99%
“…A meta-analysis of eight studies comparing the prevalences of TST positivity among household contacts of TB index cases found a lower rate of TST positivity among contacts of HIV-infected than among contacts of HIV-uninfected index TB cases (64). A cross-sectional study evaluating the prevalence of positive TSTs in pediatric contacts of adults with TB and HIV infection in Botswana found a lower proportion of TST positivity in children exposed to adult index cases with CD4 counts of Ͻ200 cells/l than in those exposed to index cases with CD4 counts of Ն200 cells/l (145).…”
Section: Does Hiv Alter the Transmission Dynamics Of Tb?mentioning
confidence: 99%
“…Whether HIV-infected patients with tuberculosis are more or less infectious than HIV-uninfected patients with tuberculosis has been debated for years, with studies supporting both more and less transmission from HIV-infected patients, compared with HIV-uninfected patients [14]. Escombe et al [3] suggest that the HIVinfected patients in their cohort were more infectious for tuberculosis than were the HIV-uninfected patients studied by Riley et al [6][7][8]15] during the 1950s.…”
mentioning
confidence: 99%
“…Similarly, recent work from sub-Saharan Africa has shown that a significant number of new cases of tuberculosis, and recurrent cases of tuberculosis, also result from recent transmission (Sonnenberg et al 2001). Meta-analysis of several studies of health care workers who had contact with tuberculosis patients suggest that patients with tuberculosis co-infected with HIV are not more intrinsically more infectious than are HIV-l negative tuberculosis patients (Cruciani et al 2001). …”
Section: Tuberculosis and Hiv: Epidemiological Considerationsmentioning
confidence: 98%